The Fact of Domestic Violence a Case Report - Sözen, Mehmet Şevki; Elmas, İmdat and Sözen, Atiye and Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 1999)
Domestic violence, inspite of interpersonal cultural, social and economical changes, most frequently appears as various explotative behaviours against women, because it is generally based on a male-dominant ideology determining social rules and on domination of men to women. The case presented is 25 years old, married for 3 years and a university graduate, and has applied to Istanbul Medical Faculty, Forensic Medicine Department with a statement of physical and sexual abuse. During the examination in our department, some common trauma findings were detected and existing lesions were recorded by camera. With the psychiatric consultation, the present findings relating to the person diagnosed with Posttraumatic Stress Disorder, have been agreed to be consistent with the domestic violence history. In our study, we discussed the significance and the role of the fact that, beside the physical findings, psychiatric evaluation must also be taken into consideration in the assesment of such phenomena, in determining the result of the report to be issued. Key Words: Domestic violence, Physical trauma, Posttraumatic stress disorder.